A SWOT Generated Thematic Analysis of the Perceptions of Staff on the Effectiveness of Knowledge Management Application in Township Schools - Bongani Innocent Nkambule (People and Behavior Analysis, 2023)
Knowledge management (KM) ensures that schools do not forfeit a wealth of tacit knowledge assets that dwell in the minds of individual members of staff. It also ensures that this knowledge is not only externalised but is also documented and deposited into the institutional memory or repository for it to be retrieved and re-used at a later stage. The quantum of this qualitative study was informed by the paucity of literature on the role of KM in South African schools. It adopted a SWOT (i.e., strength, weaknesses, opportunities, and threats) analysis both as a theoretical framework and an instrument to evaluate the effectiveness of KM application in two township schools in the locality of Emalahleni in Mpumalanga province. The study revolved around a sample of 14 participants drawn from populations of teachers, administrative clerks, heads of departments (HoDs), and principals. The social constructivist element of the study meant that the researcher took part in understanding participants' constructions of their realities about KM application in their schools. As far as the internal dynamics of the studied schools were concerned, it transpired that even though both schools had supportive school governing bodies, and reasonably efficient ICT infrastructure and connectivity, much of the KM weaknesses were caused by anti-collaborative knowledge-exchange practices, the erosion of Ubuntu-directed ethical undertakings, ill-treatment of administrative staff by teachers and HODs, and principals' inaccessibility to the workforce at a lower level; all of which contributed to teacher absenteeism, low staff morale, knowledge hoarding, poor communication of policies and loss of tacit knowledge. The study also presents tabulated findings of the kinds of threats that schools can guard themselves against and the opportunities they can tap into in order to leverage KM.